Edukasi Personal Branding bagi Siswa SMA Carnegie Medan di Era Digital - Sjukun Sjukun; Wily Julitawaty; Fenny Fenny; Yusuf Taufik (Jurnal Pemberdayaan Masyarakat, 2025)
This community service activity focused on enhancing the understanding and skills of Carnegie High School students in Medan in building personal branding in the digital era. With the rapid development of technology and the dominance of social media in daily life, positive personal branding has become a crucial factor for individual success, both in education and future career prospects. This activity was implemented as a short 1-hour workshop adopting an interactive and participatory approach, involving 40 students from grades X and XI. The workshop included a material presentation session covering the definition, importance of self-image, and use of digital platforms, followed by practical exercises such as creating a